The respiratory virus pathogen spectrum and genetic characteristics of influenza A(H1N1)pdm subtype viruses in Guizhou province, 2022 - 2023 - Li ZHUANG; Qian KE; Ju ZHENG; Ping WU; Weijia JIANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the composition of the respiratory virus pathogen spectrum of influenza-like cases in Guizhou province from 2022 to 2023, and to further analyze the genetic characteristics and variation patterns of influenza A (H1N1) pdm subtype viruses. MethodsA total of 519 influenza-like cases were collected in Guizhou province from 2022 to 2023. Multiplex fluorescent quantitative PCR was used to detect common respiratory pathogens, including influenza viruses (IFV), parainfluenza viruses (HPIV), coronaviruses (HCoV), respiratory syncytial virus (RSV), adenovirus (ADV), human metapneumovirus (HMPV), rhinovirus (HRV), and bocavirus (HBoV), as well as their subtypes. SPSS 22.0 was used for data analysis of the detection results. High-throughput sequencing technology was used to determine the whole genome sequences of influenza A (H1N1) pdm subtype viruses. Nextclade and MEGA7 were used to analyze the hemagglutinin (HA) gene sequences and the mutations in glycosylation sites, antigenic determinants, and receptor-binding sites. ResultsA total of 363 positive samples were detected, with an overall positive rate of 61.42%. The top three detection rates were IFV-A (H1N1) pdm subtype viruses (positive rate 15.06%, 89 cases), IFV-A (H3N2) subtype viruses (positive rate 13.71%, 81 cases), and SARS-CoV-2 (positive rate 13.37%, 79 cases). The P-values for the detection rates of respiratory pathogens in different genders and age groups were 0.119 and 0.078, respectively, with P > 0.05, indicating no statistically significant differences. The detection rate of respiratory pathogens in different seasons was P < 0.001, showing a statistically significant difference. A total of 36 cases of mixed infections were detected, with a detection rate of 6.09%. Rhinovirus mixed infections were the most common (17 cases, accounting for 47.22%). A total of 16 whole genome sequences of influenza A(H1N1)pdm09 subtype viruses from Guizhou province were obtained, all belonging to the 6B.1A.5a.2a evolutionary branch. The Sb antigenic determinant underwent A186T and Q189E amino acid substitutions. The receptor-binding site underwent mutations in the 190-helix (184-191): A186T, Q189E, and the 220-loop E224A. No changes in glycosylation sites were found. ConclusionRespiratory viruses are important pathogens in influenza-like cases, with influenza viruses being the most common. The proportion of mixed infections is relatively high. IFV and HMPV detection rates show significant seasonal differences. The molecular structure and function of influenza A(H1N1)pdm09 subtype viruses in Guizhou province from 2022 to 2023 have not undergone major changes, and they match well with the vaccine strains, indicating good antibody protection from influenza vaccines.